The Cultural Identity and Traditional Food in Timor Leste - Jose Barreto; Januario Maria Neto Mok; Antonio Guterres (Green Publisher Indonesia, 2024)
The despite centuries of colonization and multiple occupations, along with the current white noise of popular culture, East Timor have to get back in touch with its heritage especially food – for the well-being of its people and a potential tourism bounty. The traditional food is needed to be set into the school curriculum. To facilitate the research team in this study, in order to run systematically, Bogdan was used in Sugiono, which is the process of finding and compiling systematically the data obtained from interviews, field notes, international conferences, seminars, and other materials, so that it can be easily understood and the findings can be informed to others, qualitative data analysis is inductive, namely analysis based on the data obtained. There has never been an established book-reading or textbook-learning tradition in Timor-Leste ). The youth are “active practitioners of popular culture” … and “not interested in having the traditional approach”. Survey data among Indian youth revealed that they were “astounded by Western culture”, and were influenced by it in several areas that included Western Culture (32% strongly agreed; 29% agreed), music (36%; 31%), trends (29%; 26%), behavior (23%; 17%), and ideology (23%; 14%).